2021
DOI: 10.1186/s12871-021-01368-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of exhaled propofol with Narcotrend index and calculated propofol plasma levels in children undergoing surgery under total intravenous anesthesia - an observational study

Abstract: Background Exhaled propofol concentrations correlate with propofol concentrations in adult human blood and the brain tissue of rats, as well as with electroencephalography (EEG) based indices of anesthetic depth. The pharmacokinetics of propofol are however different in children compared to adults. The value of exhaled propofol measurements in pediatric anesthesia has not yet been investigated. Breathing system filters and breathing circuits can also interfere with the measurements. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…But the correlations were not good in all studies. In pediatric patients, Heiderich et al used MCC-IMS to demonstrate moderate correlations between exhaled propofol concentration and the Narcotrend Index [30]. The study of Braathen et al found that the modest correlation whether in normal-weight or obese surgical patients makes the bedside online IMS device's everyday clinical usefulness questionable [31].…”
Section: Discussionmentioning
confidence: 99%
“…But the correlations were not good in all studies. In pediatric patients, Heiderich et al used MCC-IMS to demonstrate moderate correlations between exhaled propofol concentration and the Narcotrend Index [30]. The study of Braathen et al found that the modest correlation whether in normal-weight or obese surgical patients makes the bedside online IMS device's everyday clinical usefulness questionable [31].…”
Section: Discussionmentioning
confidence: 99%
“…The NI was originally developed as an EEG-based monitoring modality for general anesthesia and correlates with the minimal alveolar concentration of sevoflurane and exhaled propofol during anesthesia [ 18 , 19 , 20 ]. During transition from induction to maintenance, the use of NI can help to reduce the use of intraoperative propofol [ 21 ] and guide sedation depth during endoscopies under an opiate and propofol [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that maintaining an intraoperative bispectral index (BIS) value of 30-40 is more conducive to the recovery of early postoperative cognitive function. In this study, a metaanalysis was conducted to systematically evaluate the impact of different BIS values on POCD in order to provide a clinical reference [3].…”
Section: Introductionmentioning
confidence: 99%